Automatic activation of sounds by letters occurs early in development but is not impaired in children with dyslexia - Clayton, F; Hulme, C (Taylor and Francis, 2017)
The automatic letter-sound integration hypothesis proposes that the decoding difficulties seen in dyslexia arise from a specific deficit in establishing automatic letter-sound associations. We report the findings of 2 studies in which we used a priming task to assess automatic letter-sound integration. In Study 1, children between 5 and 7 years of age were faster to respond to a speech-sound when primed by a congruent letter, indicating that automatic activation of sounds by letters emerges relatively early in reading development. However, there was no evidence of a relationship between variations in the speed of activating sounds by letters and reading skill in this large unselected sample. In Study 2, children with dyslexia demonstrated automatic activation of sounds by letters, though they performed slowly overall. Our findings do not support the theory that a deficit in automatic letter-sound integration is an important cause of reading difficulties but do provide further evidence for the importance of phonological skills for learning to read.